Atmospheric turbulence estimation for helicopter flight control system design - Olivo, N.; Cortigiani, N.; Panza, S.; Lovera, M.; Del Gobbo, D. (My University, 2017)
Verification of Flight Control System (FCS) design against stabilization and performance requirements in turbulence faces an awkward problem: the FCS is designed to reject disturbances and this makes it difficult to evaluate the actual turbulence level from flight test data. As a matter of fact, it is not possible to assess the FCS performance at different turbulence levels if it is not possible to have a reliable evaluation of the turbulence level itself. A good FCS design will counteract the effect of turbulence on aircraft attitude and rates by means of a very energetic control action. Hence, the turbulence level can be estimated by processing the residual aircraft upset and the FCS control action. This paper describes the design and validation of an atmospheric turbulence estimator used for the design of a helicopter FCS.